The GBS dataset: measurements of satellite site diversity at 20.7 GHz in the UK. (17th March 2013) - Callaghan, S. A.; Waight, J.; Agnew, J. L.; Walden, C. J.; Wrench, C. L.; Ventouras, S.
<x xml:space="preserve">Abstract</x> The GBS (Global Broadcast Service) dataset is a series of radio attenuation measurements made at three sites in the UK: Chilbolton and Sparsholt, both in southern UK, and Dundee in Scotland. The aim of the experiment was to make long term measurements of the signal strength received from a 20.7 GHz beacon on the US Department of Defense satellite UFO‐9 at multiple sites, in order to determine whether the use of site diversity as a fade mitigation technique would be effective. The dataset spans a period of 3 years, from August 2003 to August 2006 with signal attenuation sampled once per second.